2021
DOI: 10.1186/s12884-021-03877-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice to prevent COVID-19 and its associated factors among pregnant women in Debre Tabor Town Northwest Ethiopia, a community-based cross-sectional study

Abstract: Background Coronavirus disease is now a global concern with the non-availability of antiviral treatment and attacks all groups of the population. Hence, applying preventive measures is the most critical intervention to control the infection. Pregnant women are particularly susceptible to respiratory pathogens because of their immunosuppressive state and physiological adaptive change during pregnancy. Therefore, this study was aimed to assess knowledge and practice to prevent coronavirus disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
20
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 16 publications
(9 reference statements)
9
20
7
2
Order By: Relevance
“…On the contrary, the findings from previous studies done in Wollega Zone (43.6%), 42 Debre Tabor (47.6%), 43 Ghana (46.6%), 44 and low-resource African settings (30.3%) 33 which were lower than our finding. The possible discrepancy might be the difference in the study setting, socio-demographic characteristics, and study participants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the findings from previous studies done in Wollega Zone (43.6%), 42 Debre Tabor (47.6%), 43 Ghana (46.6%), 44 and low-resource African settings (30.3%) 33 which were lower than our finding. The possible discrepancy might be the difference in the study setting, socio-demographic characteristics, and study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with the study conducted in Nigeria and Debre Tabor; women’s Knowledge on COVID-19 had a substantial impact on the attitude and practice of the preventive measures. 29 , 43 , 48 The reason for this could be that knowing about COVID-19 preventive measures enhances the level of understanding about its consequences, which in turn determines to have good compliance.…”
Section: Discussionmentioning
confidence: 99%
“…According to 2019 data from the town health department, there were a total of 19,936 households (HH) and 85,727 peoples of which 49.6% (42,521) and 50.4% (43,206) were men and women, respectively. Of the total 43,206 women, 20.96% (17,968) are found in childbearing age group (i.e., 15–49 years; Ayele, Mihretie, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Research conducted by Shivanagappal [21], Awad et al [25], Nwafor et al [26], Aghababaei et al [27], Alemu Degu et al [28] also found that the knowledge of pregnant women about the transmission of COVID-19 was high. On the other hand, research conducted by Fikadu et al [29] and Ayele et al [30] found that the knowledge and practice of pregnant women regarding COVID-19 were poor.…”
Section: Discussionmentioning
confidence: 96%